المعسكر الشيوعي والثورة الجزائرية 1954 - 1962 - حياة نموسة; هناء العوز (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة إلى التعرف على موقف المعسكر الشيوعي من الثورة الجزائرية، من خلال تحليل مواقفالدول الشيوعية الكبرى، وعلى رأسها الاتحاد السوفيتي، من كفاح الشعب الجزائري ضد الاستعمار الفرنسي. من أجل تحقيق أهداف الدراسة، تم الاعتماد على المنهج التاريخي التحليلي من خلال تحليل الوثائق التاريخية والمواقف السياسية المعلنة خلال الثورة (1954–1962). وركّزت الدراسة على تتبع تطوّر مواقفوالدول الشيوعية من الثورة الجزائرية في مختلف مراحلها. تم التوصل إلى أن الدول الشيوعية، فقد أظهرت الدراسة أن الاتحاد السوفيتي والدول المنضوية ضمن المعسكر الشيوعي دعمت الثورة الجزائرية دبلوماسيًا وسياسيًا في المحافل الدولية، لا سيما الأمم المتحدة، كما قدّمت بعض الدول دعمًا تقنيًا ولوجستيًا محدودًا للثوار الجزائريين. أظهرت الدراسة النتائج التالية: • شكلت جبهة التحرير الوطني الإطار الوحيد المعترف به من قبل الشعب والثوار، ورفضت أي عمل مسلح خارج عنها. • المعسكر الشيوعي، رغم حذره، لعب دورًا داعمًا سياسيًا وأيديولوجيًا للثورة على المستوى الدولي." "This study aims to examine the position of the Communist bloc toward the Algerian Revolution by analyzing the stances of major communist countries—most notably the Soviet Union—regarding the Algerian people's struggle against French colonialism. To achieve the study’s objectives, the historical-analytical method was adopted, relying on the analysis of historical documents and official political statements issued during the revolution (1954–1962). The study focused on tracking the evolution of the positions taken by communist states throughout the different phases of the Algerian Revolution. The findings reveal that the Soviet Union and other countries within the Communist bloc provided political and diplomatic support to the Algerian Revolution, particularly within international platforms such as the United Nations. Some countries also offered limited technical and logistical assistance to Algerian fighters. The main conclusions of the study include: • The National Liberation Front (FLN) emerged as the sole legitimate framework recognized by the Algerian people and fighters, rejecting any armed movement outside its structure. • Despite its initial caution, the Communist bloc played a supportive political and ideological role for the Algerian cause at the international level."
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: جبهة التحرير الوطني; الاتحاد السوفيتي; الحزب الشيوعي الجزائري; الثورة الجزائرية; المعسكر الشيوعي; Communist bloc; Algerian Revolution; Algerian Communist Party; Soviet Union; National Liberation Front.